HUBUNGAN TINGKAT PENGETAHUAN PASIEN TENTANG PERAWATAN LUKA PASCA PENCABUTAN GIGI GERAHAM 3 DENGAN KEBERHASILAN PERAWATAN LUKA PASIEN (Poltekkes Kemenkes Bandung, 2022)
Post-extraction of M3 tooth extraction is an effort to speed up the healing process and prevent and reduce pain and swelling. Pasien will be given instructions and education on how to take care of the possible tooth extractions. In-depth knowledge of the treatment of M3 tooth extraction wounds can be known in the instruction after removal. This study aims to determine the relationship between the level of patient knowledge about wound care after the removal of molars 3 with the success of wound care at the Dental and Oral Hospital, Padjadjaran University. This type of research is analytics. The research sample was taken by accidental sampling with a total population of 31 respondents who performed M3 tooth extraction at the Minor Surgical Poly of the Dental and Oral Hospital, Padjadjaran University. The results showed that respondents who had a level of knowledge of post-revocation wound care in the good category were 12 people (38.7%). The results of wound treatment of respondents after tooth extraction M3 in the normal wound healing category were 15 people (48.8%). There is a relationship between the level of knowledge of m3 tooth extraction wound care and the success of wound care p(0.03<0.05).